Characterization of inner structure of limestone by X-ray computed sub-micron tomography. (20th June 2018) - Kalasová, Dominika; Dvořák, Karel; Slobodník, Marek; Všianský, Dalibor; Zikmund, Tomáš; Dluhoš, Jiří; Váňa, Rostislav; Bureš, Jaroslav; Kaiser, Jozef
Highlights: X-ray computed tomography (CT) is used to visualize limestone inner structure. Limestone containing coarser cement of calcite with fluid inclusions is studied. Characterization of material is performed by classical petrographic methods. 3D distribution of fluid inclusions and air voids in volume is shown by CT. CT data are correlated with light microscopy and 3D EDS analysis using FIB-SEM. Abstract: Limestones are fundamental industrial and building materials. Sparry calcite as a principal petrographic component of limestones can contain fluid inclusions. A certain amount of fluid inclusions directly influences decrepitation which plays an important role in decarbonisation processes. In this paper, a limestone with a high content of fluid inclusions and carbon was investigated. Presence of chlorine and alcalic elements was confirmed with microthermometry, mineralogical and chemical analyses. X-ray computed tomography with sub-micron resolution (CT) was applied to obtain a 3D distribution of cavities. CT data were correlated with some light microscopy images and also with the same sample's tomography data which were gathered using the 3D X-ray energy dispersive spectroscopy (3D EDS) by a scanning electron microscope equipped with a focused ion beam (FIB-SEM). The latter further determined dolomites and metals in the CT data of limestone.